Simulation of Slag–Matte/Metal Equilibria for Complex and Low-Grade Raw Materials - Pekka Taskinen (MDPI AG, 2021)
The depleting and increasingly complex mineral resources bring challenges into the area of metal production, bringing new boundary conditions to the smelting and refining processes. Thermodynamics of phases and equilibria are the key to the analysis of pyrometallurgical processes, enabling descriptions of their limiting boundary conditions. The raw material basis of non-ferrous metals needs an effective control of iron oxide fluxing due to the challenging fact that the targeted metal values of, e.g., copper, nickel, lead, and tin will exist as minority components in the smelter feeds compared to iron sulphides, gangue, and many harmful elements. This means more complex slag compositions and the amount of produced slag being several times that of the metal production. This feature severely impacts the heat balance of the smelting vessels where autogenous operation without external fuels becomes more and more difficult to maintain.